Association between neutrophil percentage-to-albumin ratio and 3-month functional outcome in acute ischemic stroke patients with reperfusion therapy - Cui, Ting; Wang, Changyi; Zhu, Qiange; Li, Shucheng; Yang, Yuan; Wang, Anmo; Zhang, Xuening; Shang, Wenzuo; Wu, Bo (Frontiers in Neurology, 2022)
Abstract Background: Neutrophils and albumin are associated with outcomes in acute ischemic stroke (AIS) patients. We aimed to explore the association between the neutrophil percentage-to-albumin ratio (NPAR), a novel marker of inflammation and oxidative stress, and the 3-month functional outcome in AIS patients with reperfusion therapy. Methods: This single-center, retrospective cohort study consecutively enrolled AIS patients with reperfusion therapy. Neutrophils and albumins were collected on admission. The primary outcome was poor functional outcome, which was defined as a modified Rankin scale score of 3 to 6 at 3 months. Results: A total of 647 AIS patients who received reperfusion therapy were analyzed. The mean age was 68.9±13.9 years, and 358 (55.3%) patients were males. The median NPAR was 1.89 (IQR 1.64-2.09). The percentage of patients with 3-month poor functional outcome was 57.0% (369/647). NPAR was positively associated with poor functional outcome (OR 2.76, 95% CI 1.52-5.03, P=0.001). When patients were classified into tertiles, patients in the upper tertile (2.03-7.59) had a higher risk of poor outcome than patients in the lower tertile after adjusting for potential confounders (0.78-1.73) (OR 2.10, 95% CI 1.28-3.42, P=0.003). The risk of poor outcome increased with NPAR tertiles (P-trend =0.003). The optimal cut-off value of the NPAR for predicting poor outcome was 1.72, with a sensitivity of 0.75 and a specificity of 0.43. Conclusion: NPAR was significantly associated with 3-month poor functional outcomes in AIS patients who received reperfusion therapy.